SIGNIFICANCE OF SEMICONDUCTOR POLYMERS IN NOWADAYS. REVIEW - Djuraeva U.G.; Djuraev G.G.; Khodjamkulov S.Z. (Ta’lim innovatsiyasi va integratsiyasi, 2024)
In this article, we consider the processes for the production of semiconducting polymers for students of higher and secondary special education.